SOSIALISASI PEMANFAATAN PLTS DALAM PENINGKATAN PRODUKTIFITAS DAN KESEJAHTERAAN MASYARAKAT DI DESA PA’BATANGAN - Jusnawati, Jusnawati; Sunaniah, Sunaniah; Khaidir, Muhammad; Jamaluddin, Jamaluddin; Syafrun, Muhammad (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the important and vital needs for modern society is electrical energy. Electrical energy needs that cannot be met will certainly greatly disrupt the continuity of the community's socio-economic activities. This is felt acutely in several remote areas due to the lack of electrical energy. This service aims to provide understanding and increase awareness of the Takalar community regarding the use of Solar Power Plants as an alternative energy source, and can support community productivity and welfare. The methods used include outreach with interactive discussions and simulations of PLTS assembly based on community needs in the fields of agriculture and home lighting. The main targets of this service activity are the people of Pa'batangan village, Mappakasunggu subdistrict, Takalar district and the local government. The results of the activity show an increase in understanding and awareness of the community and government regarding the importance of using PLTS in supporting the fulfillment of community electricity needs and the socio-economic impacts they cause. This socialization is expected to increase understanding and awareness. and the skills of the community and government regarding the use of PLTS which can support the improvement and welfare of the people of Takalar district.